The Association between Symptom Accommodation and Emotional Coregulation in Couples with Binge Eating Disorder. Issue 4 (19th September 2018) - Weber, Danielle M.; Fischer, Melanie S.; Baucom, Donald H.; Baucom, Brian R. W.; Kirby, Jennifer S.; Runfola, Cristin D.; Matherne, Camden E.; Bulik, Cynthia M.
Abstract : Intense negative emotions and maladaptive behavioral strategies to reduce emotional distress occur not only in patients with various forms of psychopathology but also in their committed partners. One common strategy to reduce distress is for partners to accommodate to the symptoms of the disorder, which reduces distress short term but maintains symptoms long term. Accommodation is believed to be motivated by the partner reacting behaviorally to the patient's emotions, but the emotions of the partner in this context have yet to be examined. This pilot study examined how partner accommodation related to specific patterns of emotional coregulation between patients with binge eating disorder (BED) and their partners, before and after a couple‐based intervention for BED. Vocally encoded emotional arousal was measured during couples' ( n =  11) conversations about BED. As predicted, partners' emotional reactivity to patients' emotional arousal was associated with high accommodation before treatment. Thus, partners may use accommodation as a strategy to reduce both the patients' and their own distress. After treatment, partners' arousal was no longer associated with the patients' emotional arousal; instead, partners showed greater emotional stability over time, specifically when accommodation was low. Additionally, patients were less emotionally aroused after treatment. Therefore, treatment may have decreased overall emotionality of patients and altered the association between accommodation and partners' emotional reactivity. If replicated, this understanding of the emotional context associated with accommodation in BED can inform couple‐based treatment by targeting specific emotional precipitants of behaviors that maintain symptoms. Resumen: La emociones negativas intensas y las estrategias conductuales desadaptativas para reducir el distrés emocional se producen no solo en pacientes con varias formas de psicopatología, sino también en sus parejas estables. Una estrategia común para disminuir el distrés es que las parejas se adapten a los síntomas del trastorno, lo cual reduce el distrés a corto plazo pero mantiene los síntomas a largo plazo. Se cree que la adaptación está motivada por la reacción conductual de la pareja a las emociones del paciente, pero las emociones de la pareja en este contexto aún no se han analizado. Este estudio piloto examinó cómo la adaptación de la pareja está relacionada con patrones específicos de corregulación emocional entre los pacientes con trastorno por atracón de alimentos y sus parejas, antes y después de una intervención en la pareja por trastorno por atracón de alimentos. Se midió la excitación emocional codificada en la voz durante conversaciones de las parejas (n = 11) acerca del trastorno por atracón de alimentos. Como se anticipó, la reacción emocional de las parejas a la excitación emocional de los pacientes estuvo asociada con una alta adaptación antes del tratamiento. Por lo tanto, las parejas pueden usar la adaptación como estrategia para reducir tanto el distrés de los pacientes como el propio. Después del tratamiento, la excitación de las parejas dejó de estar asociada con la excitación emocional de los pacientes. En cambio, las parejas demostraron una mayor estabilidad emocional con el tiempo, específicamente cuando la adaptación fue baja. Además, los pacientes estuvieron menos excitados emocionalmente después del tratamiento. En consecuencia, el tratamiento pudo haber disminuido la emocionalidad general de los pacientes y modificado la asociación entre la adaptación y la reacción emocional de las parejas. Si se reproduce, esta comprensión del contexto emocional asociada con la adaptación en los trastornos por atracón de alimentos puede fundamentar el tratamiento basado en la pareja abordando precipitantes emocionales específicos de conductas que mantienen los síntomas. 摘要 : 强烈负面情绪和不良适应行为策略来降低情绪困扰不仅发生在各种精神病患者中间, 而且发生在其稳定伴侣中间。一个常见减轻困扰的策略是伴侣适应紊乱症状, 这会减轻短期困扰但长期症状维持不变。适应被认为是伴侣行为上对患者情绪反应所激发, 然而在这一背景下伴侣的情绪还没有研究. 该试点研究考察了以伴侣为基础的针对过食症干预措施之前和之后伴侣适应如何与过食症患者和其伴侣情绪共同管理特定模式相关联。我们在伴侣双方(n = 11)关于过食症进行对话过程中测量了通过声音加码的情绪唤醒。和预期一样, 配偶对于患者情绪唤醒和情绪反应和治疗前高度适应相关。因此, 伴侣可能使用适应作为一种策略来降低患者以及自身困扰。治疗后, 伴侣唤醒不再和患者情绪唤醒相关联。相反, 伴侣表现出更强的长期情绪稳定性, 特别是当适应较低时。此外, 患者在治疗后情绪唤醒较少。因此, 治疗可能会总体降低患者情绪化并改变适应和伴侣情绪反应之间的关联。如果通过复制, 对于过食症适应情绪背景的这一理解可以通过针对特定维持症状行为情绪促使因素来影响伴侣为基础的治疗。